Magnesium Alleviates Adverse Effects of Lead on Growth, Photosynthesis, and Ultrastructural Alterations of Torreya grandis Seedlings - Shen, Jie; Song, Lili; Müller, Karin; Hu, Yuanyuan; Song, Yang; Yu, Weiwu; Wang, Hailong; Wu, Jiasheng (Frontiers in Plant Science, 2016)
Magnesium (Mg2+) has been shown to reduce the physiological and biochemical stress in plants caused by heavy metals. To date our understanding of how Mg2+ ameliorates the adverse effects of heavy metals in plants is scarce. The potential effect of Mg2+ on lead (Pb2+) toxicity in plants has not yet been studied. This study was designed to clarify the mechanism of Mg2+-induced alleviation of lead (Pb2+) toxicity. Torreya grandis (T. grandis) seedlings were grown in substrate contaminated with 0, 700 and 1400 mg Pb2+ per kg-1 and with or without the addition of 1040 mg kg-1 Mg2+. Growth parameters, concentrations of Pb2+ and Mg2+ in the plants’ shoots and roots, photosynthetic pigment, gas exchange parameters, the maximum quantum efficiency (Fv/Fm), root oxidative activity, ultrastructure of chloroplasts and root growth were determined to analyze the effect of different Pb2+ concentrations on the seedlings as well as the potential ameliorating effect of Mg2+ on the Pb2+ induced toxicity. All measurements were tested by a one-way ANOVA for the effects of treatments. The growth of T. grandis seedlings cultivated in soils treated with 1400 mg kg-1 Pb2+ was significantly reduced compared with that of plants cultivated in soils treated with 0 or 700 mg kg-1 Pb2+. The addition of 1040 mg kg-1 Mg2+ improved the growth of the Pb2+-stressed seedlings, which was accompanied by increased chlorophyll content, the net photosynthetic rate and Fv/Fm, and enhanced chloroplasts development. In addition, the application of Mg2+ induced plants to accumulate five times higher concentrations of Pb2+ in the roots and to absorb and translocate four times higher concentrations of Mg2+ to the shoots than those without Mg2+ application. Furthermore, Mg2+ addition increased root growth and oxidative activity, and protected the root ultrastructure. To the best of our knowledge, our study is the first report on the mechanism of Mg2+-induced alleviation of Pb2+ toxicity. The generated results may have important implications for understanding the physiological interactions between heavy metals and plants, and for successful management of T. grandis plantations grown on soils contaminated with Pb2+.